People of the Earth: Trans-Traditional Dialogue in Christian Perspective - ., JOD (Journal of Dharma, 1980)
Charles W. Swain, People of the Earth : Trans-Traditional Dialogue in Christian Perspective, New Delhi, Islam and the Modern Age Society, 1976, pp. xi + 123.